Liquid rocket engine thrust chamber : parametrical modeling - Rezende, Rene Nardi (Society of Automotive Engineers, 2018)
This book presents an innovative parametric model applicable to the project of some elements of the liquid rocket thrust chamber with the level of detail and accuracy appropriate to the preliminary design phase. It addresses the operating characteristics and dimensioning of some thrust chamber elements through a set of equations and parameters, which include thrust or propellant characteristics. The model degree of sophistication was adjusted to the requirements of the Project Life Cycle Phase B, while also enabling quick analysis of new configurations from changes in initial project parameters.
Title from PDF title page (SAE Web site, 01/15/2019)
Keywords: Space vehicles -- Propulsion systems.; Rockets (Aeronautics); elektronické knihy; electronic books